Assessment of Organizational and Technological Reliability Monolithic Works - Stepanov, Aleksander (International Journal of Sustainable Construction Engineering and Technology, 2024)
Every year in the construction process new technologies are introduced, the use of new building materials increases, a large number of contractors are involved, with a significant increase in the scale of construction and the need to ensure the reliability of construction. There arises a necessity to forecast and correct activities of construction organizations, to give adequate assessments of the adopted organizational and technological solutions (OTS), which, as a rule, leads to a decrease in the prescriptive term of construction. Monolithic structure construction process design is closely connected with the necessity of clear and correct choice of the necessary organizational-technological solutions. Depending on the made decisions it is possible to estimate the reliability of monolithic works. This in its turn gives the possibility to forecast the terms of production, the cost of monolithic works on the stage of design of dwelling buildings and industrial objects directly. The article offers a methodology for calculating the evaluation of organizational and technical reliability of the process of monolithic structures. For the successful performance of monolithic works it is necessary to ensure the reliable functioning of all participants of the process from designers to construction teams. The article presents the calculation of organizational and technological reliability index (OTR) of monolithic works. To calculate the index the author proposed a model and introduced the concept of reliability of the considered process of monolithic works as a probability of achieving the final goal. At the same time, the process of monolithic works performance both for residential and civil objects is taken as a complex stochastic system, which includes a set of co-dependent relations. The application of the assumed approach for the calculation of organizational and technological reliability of monolithic works with small changes, refinements can be applied to the calculation of other works in the construction of buildings and structures throughout the life cycle of construction. At the same time, this methodology makes it possible to obtain a numerical value of reliability assessment, which is very relevant when choosing organizational and technological solutions.